NURSING RESEARCH PRIORITIES IN INDONESIA AS PERCEIVED BY NURSES - Lely Lusmilasari; Yupin Aungsuroch; Widyawati Widyawati; Sunisa Sukratul; Joko Gunawan; Melyza Perdana (Belitung Raya Foundation, Indonesia, 2020)
Background: To promote excellence in nursing research, setting research priorities is needed to meet the need of community aligned with the national context. Unfortunately, limited number of studies has examined nursing research priorities in Indonesia. Objective: To identify nursing research priorities in Indonesia from the perspectives of nursing experts. Methods: This was a descriptive qualitative study. Focus group discussion was conducted among participants who were purposively selected (n = 13). Data were analyzed using a consensus-based method. Results: The top ten research priority lists were identified. The priorities were nurse competence, quality of nursing care in nursing services, nursing policy, nurse work environment, nurse mobility, interprofessional education and collaboration, teaching learning evaluation, nursing career, complementary therapy in nursing, and technology and informatics in nursing. Conclusion: Findings of this study could be used as the basis of direction for development of future research in Indonesia.